Background and prospects for the translation and research of Omar Khayyam’s rubaiyat in England. - Ishankulova, Diyora (Журнал иностранных языков и лингвистики, 2023)
The article paid special attention to the discovery of Khayyam in England translation by Fitzgerald. His translations were approved by most readers. The reason for Fitzgerald’s success in English exposition of rubai Khayyam is that he relied of the principle of free translation.